2021
DOI: 10.1007/s00397-021-01281-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of shear viscosity and wall slip velocity of highly concentrated suspensions with non-Newtonian matrices in pressure driven flows

Abstract: The rheological characterization of concentrated suspensions is complicated by the heterogeneous nature of their flow. In this contribution, the shear viscosity and wall slip velocity are quantified for highly concentrated suspensions (solid volume fractions of 0.55–0.60, D4,3 ~ 5 µm). The shear viscosity was determined using a high-pressure capillary rheometer equipped with a 3D-printed die that has a grooved surface of the internal flow channel. The wall slip velocity was then calculated from the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 55 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Separating frictional and viscous resistance effects in multiphase flows using rheometers requires careful calibration and measurement. [26][27][28] Additionally, rheometers do not typically replicate microvasculature geometries or physiological oxygen tensions. To overcome these challenges, in this study we focus on time-resolved imaging of flow profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Separating frictional and viscous resistance effects in multiphase flows using rheometers requires careful calibration and measurement. [26][27][28] Additionally, rheometers do not typically replicate microvasculature geometries or physiological oxygen tensions. To overcome these challenges, in this study we focus on time-resolved imaging of flow profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Gulmus et al studied a suspension of PMMA particles in hydroxyl-terminated polybutadiene and confirmed that for increasing ϕ the slip velocity also increases [10]. These results were contradicted by the work of Haworth et al [11], where the slip velocity increased for a lower concentration of talc particles in PP compounds, while Wilms et al [12] obtained opposite results for limestone-filled suspensions made by different thickeners. The wall slip phenomenon in extrusion is complex and affected by numerous factors [13].…”
Section: Introductionmentioning
confidence: 93%
“…If the attractive interaction between the particles is strong enough, the concentrated suspension resembles a stone and its reaction is to slide along the boundary surface [95]. A real or apparent slip in shear experiments with concentrated suspensions is quite possible [96][97][98].…”
Section: Heterogeneous Displacementsmentioning
confidence: 99%